Squeezing by self induced transparency in Rb filled hollow core fibers - Zhong, Wenjia; Marquardt, Christoph; Leuchs, Gerd; Andersen, U. L.; Light, P; Couny, F.; Benabid, F. (2007 European Conference on Lasers and Electro-Optics and the International Quantum Electronics Conference, 2007)
There is great interest in photonic crystal fibers (PCFs) because of their potential for hosting highly nonlinear material. Already with material of low nonlinearity such as silica for solid core PCFs, the nonlinear properties can be utilized since high intensities of light are guided within the core. To create squeezed states, we plan to exploit the high nonlinearity of resonant Rb vapor filled in the hollow fiber core and to use self-induced transparency (SIT) solitons to avoid resonant loss. High nonlinearity is induced from the self-phase modulation of a detuned 2pi soliton. Photon-phonon interactions, which cause a significant amount of excess noise in solid core fibers, will be highly reduced in our system.<br
Keywords: Resonance; Optical fiber theory; Photonics; Crystalline materials; Fiber nonlinear optics; Optical solitons; Solids; Atom optics; Physics; Optical materials